The Comparative Study of Hedges in Theses’ Abstracts Written by English and Indonesian Graduate Programs of Universitas Negeri Semarang (The Journal of Educational Development, 2021)
Hedges, to be softened and weaken the claims, which avoid being blamed, and the claim can be accepted, play an essential role in presenting academic research in masters’ theses abstracts. This case study aimed to explain the comparison of hedges in the English and Indonesian graduate programs theses abstracts. The qualitative analysis was undertaken into five sub-research questions to find out the English department's hedges, the Indonesian department's hedges, the similarities and differences between both and its consequences. The analysis was employed based on the taxonomy of Hyland (1998) manually. The sample was thirty master’s thesis abstracts of graduate students from the English and Indonesian graduate programs Universitas Negeri Semarang, published from 2018 to 2022 and accessed through an online library. The finding reveals that hedging functions such as writer-oriented hedges, accuracy-oriented hedges, and reader-oriented hedges are realized in English, and Indonesian thesis abstracts are mostly similar. Besides, the analysis finds some differences. One of them is the similar term employed to reach different hedging pragmatic functions. The study's finding concludes that the English graduate program tends to use writer-oriented hedges more, expressing the unwillingness of the writers to be seen entirely in their propositions. In contrast, the Indonesian graduate program tends to engage the readers by utilizing reader-oriented hedges more often than English graduate program students.